Hubungan antara Work Life Balance dengan Burnou pada Perawat - de Jong, Elvira; Titi Pratitis, Niken; Yul Arifiana, Isrida (Journal of Comprehensive Science, 2025)
Burnout, which is characterized by emotional exhaustion, depersonalization, and decreased personal achievement, is a major challenge for mental health nurses at Ambon Hospital. This study aims to analyze the relationship between Work-Life Balance (WLB) and burnout, with the hypothesis that a better WLB can lower the burnout rate. The study used a quantitative correlational approach, with data collected from 127 nurses through a structured questionnaire. Data analysis was carried out using the Spearman Rank Correlation method to identify the relationship between variables. The results showed a significant negative association between WLB and burnout (r = -0.559, p < 0.05), indicating that the better the work-life balance, the lower the risk of burnout. These findings emphasize the importance of supportive time management strategies and work environments to improve the mental well-being and productivity of nurses. The study also provides recommendations for health organizations to prioritize programs that support work-life balance. Further research is recommended to involve a wider population and use a longitudinal approach to gain deeper insights into the factors that affect burnout in the health work environment.